Consumer Value Creation in the Consumption of Luxury Goods: A Consumer Perspective - Benvie-Ferreiros, Lidia (2008)
The globalisation of the luxury market has presented the industry with an ever expanding and broad range of global consumers that are facilitating significant growth to the industry. In light of the downturn in Western economies, the extension and demand for luxury goods in booming Eastern economies present the luxury industry with a rosy future, estimated to be worth over $450 billion by 2012. The nature of this growth has been down to changing consumption behaviour of consumers; no longer exclusively for the wealthy, the market for luxuries is increasingly evident in both middle- and lower-income brackets. This has been the result of numerous demographic, socio-economic and global trends within the industry and its expansion into the markets of developing countries. In light of this evidence, indicating the extreme demand and influence of this industry, it is surprising that little has been written on the topic by academics. The luxury industry is faced with multifaceted and pertinent areas posing as current challenges. The democratisation of luxury through the internet has developed issues for luxury brand owners in controlling their adopters and information regarding the brand and her products online. Facing difficulty in controlling consumer surfing habits, this has been suggested to pose a severe threat to the exclusivity and rarity luxury brands rely upon. Other challenges threatening the luxury industry include counterfeiting, inappropriate adopters, sustainability and overextensions, each providing their own set of pertinent issues that threaten the success of this industry. In addition to these mounting trends and threats to the luxury industry, luxury brand owners are too being faced with morphing consumer value paradigms that are ever more demanding in the case of luxury brands. The need to better understand their consumers in order to provide superior value to them by improving the luxury brand consumer experience is of precedence. In exploring the consumer value paradigm for luxury branded goods from a consumer perspective this research hopes to provide an entrenched understanding of how value for these goods is formed. Furthermore, by doing so, it is hoped that the findings can provide luxury brand owners with new perspective to better understand this formulation of value to their products, and furthermore, augment this value. The research objectives of this study on consumer value in luxury goods therefore seek to find consumer perceptions of luxury brand value and how these can be categorised. Building on the works of Smith and Colgate (2007) and Vigneron and Johnson (1999) key perceived luxury values shall be noted. The study aims to provide better understanding of the consumer value paradigm for luxury goods to benefit luxury brand owners in administering value adding operations for their consumers. Therefore analysis of the consumption process will be entailed to specifically address the gaps within the literature that other authors have highlighted as key in understanding luxury brand consumer value; the Service-Dominant approach to marketing luxury brands.